Targeting programmed cell death pathways: emerging therapeutic strategies for diabetic kidney disease - Wang, Lin; Ding, Shaowei; Hu, Yuxin; Su, Jiaming; Zhu, Gegongming; Hong, Hanzhang; Hou, Baoluo; Dong, Zhaoxi; Xue, Zeyu; Wang, Jiayi; Liu, Zhongjie; Liu, Hongfang; et al. (Frontiers in Endocrinology, 2025)
Diabetic kidney disease (DKD) is a leading cause of kidney failure. However, its pathogenesis remains incompletely understood, hindering the development of effective treatments. In recent years, substantial evidence has indicated that abnormal programmed cell death (PCD), including apoptosis, pyroptosis, ferroptosis, and autophagy, plays a crucial role in the progression of DKD, particularly in intrinsic renal cells such as podocytes, tubular epithelial cells, and mesangial cells. Novel therapeutic agents, such as sodium-glucose cotransporter 2 (SGLT2) inhibitors, glucagon-like peptide-1 (GLP1) receptor agonists, dipeptidyl peptidase-4 (DPP4) inhibitors, and relevant traditional Chinese medicines and their formulations, have demonstrated significant efficacy in improving intrinsic renal cell PCD in DKD. This review aims to provide a concise overview of the four types of PCD and their relationship with DKD, with a particular focus on highlighting the therapeutic potential of targeting PCD signaling pathways in the treatment of DKD.